Assassinations for hire in Costa Rica: an analysis based on official statics - Calderón Umaña, Rodolfo (2023)
The article provides an approach to the behavior of contract killing in Costa Rica, during the years 2006-2015, for which it uses an approach based on official statistics, interviews with public officials and descriptive statistical tools. The findings demonstrate that these murders exhibit clearly defined territorial and sociodemographic patterns that mirror those of other intentional homicides in the country. Additionally, there are indications of the heterogeneity of this phenomenon and its link to the illicit drug trade. These findings provide a solid foundation for future research and the development of effective strategies for the prevention and control of this type of crime in the country.